MAKNA TEOLOGIS JANJI BERKAT DALAM KITAB KEJADIAN 12:1-9 DAN IMPLIKASINYA BAGI KONSEP PANGGILAN GEREJA MASA KINI: ANALISIS HISTORIS-KRITIS - Yenni Mangasik; Agetri Pangloli (Jurnal Salome : Multidisipliner Keilmuan, 2026)
This paper examines the theological significance of the promise of blessing in Genesis 12:1-9 and its implications for the calling of the Church today. This study uses a historical-critical approach, demonstrating that God's call to Abram was a divine initiative that led to complete obedience. The promise of blessing was not only personal but universal, making Abram a channel of blessing for the entire nation. In the historical context of the Ancient Near East, this call was revolutionary because it led Abram to abandon his social, economic, and religious systems. The results of this study that God's blessing always has a purpose. The result of this study show that the promise of blessing in Genesis 12:1-9 is purposeful and universal, and is the theological basis for the Church’s calling as a channel of blessing today.